已知x-2y=2011,求[(3x+2y)(3x-2y)-(x+2y)(5x-2y)]÷4x的值.
1个回答
原式=(9x²-4y²-5x²-8xy+4y²)÷4x
=(4x²-8xy)÷4x
=x-2y
=2011
相关问题
已知x=1,y=2,求代数式[(3x+2y)(3x-2y)-(x+2y)(5x-2y)]÷4x的值
已知3x-2y=5求代数式【6x^4+(x^3-y)^2-(x^3+y)^2】÷(-2x)^3的值
已知x/y=2/3求[5y^2/(x-2y)-x-2y]÷(x^2-6xy+9y^2)/(x-2y)的值
已知x:y=2:3,求(x^2-y^2/xy)÷[(x+y)×(x-y/x)^3]÷(x/y^2)
1.已知:x-2y=3,求[(3x+2y)(3x-2y)-(x+2y)(5x-2y)]除4x 的值
化简求值:已知x-2y=2013,求【(3x+2y)(3x-2y)-(x+2y)(5x-2y)】/4x的值
【(5x+3y)(3x+2y)+(x+3y)(x-2y)】÷(4x)其中,x=3,y=-2,化简求值.
已知x=2008,y=2006,求x-x÷{x^2-y^2/x^3+y^3[(x-x^2+y^2/y)÷(1/x-1/y
已知2x+y=4,求代数式[(x+y)2-(x-y)2-2y(x-[1/2]y)]÷4y的值.
已知2x+y=4,求代数式[(x+y)2-(x-y)2-2y(x-[1/2]y)]÷4y的值.